2018
DOI: 10.1525/elementa.267
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal community structure and primary production in Arctic and Antarctic sea ice: A synthesis

Abstract: van Leeuwe, MA, et al. 2018 Microalgal community structure and primary production in Arctic and Antarctic sea ice: A synthesis. Elem Sci Anth, 6: 4. DOI: https://doi.org/10.1525/elementa.267 IntroductionSea ice is one of the largest biomes on earth. The area covered by Arctic (15.6 × 10 6 km 2 ) and Antarctic (18.8 × 10 6 km 2 ) sea ice is roughly 4 and 5% of the global ocean surface (361.9 × 10 6 km 2 ) at their respective maximum extents (Meier, 2017;Stammerjohn and Maksym, 2017). Sea ice is a very diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
133
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 166 publications
7
133
2
2
Order By: Relevance
“…During the ice algal growth season (September to May) total integrated biomass is dominated by bottom ice algal communities. These communities mainly consist of pennate diatom species (van Leeuwe et al, ). We note that the biomass peak in autumn is vertically more uniform than the ice algal accumulation during spring.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During the ice algal growth season (September to May) total integrated biomass is dominated by bottom ice algal communities. These communities mainly consist of pennate diatom species (van Leeuwe et al, ). We note that the biomass peak in autumn is vertically more uniform than the ice algal accumulation during spring.…”
Section: Discussionmentioning
confidence: 99%
“…During winter (July to September) the highest ice algal Chl a fraction is found in the sea ice interior. This may be the result of autumnal ice accretion that traps bottom‐ice communities; that is, interior algal biomass peaks are likely to resemble residual autumn ice algal blooms that got incorporated into the ice interior due to ice growth over autumn and winter (Grossi & Sullivan, ; Günther & Dieckmann, ; van Leeuwe et al, ). The presence or absence of interior biomass peaks may be attributed to fast‐ice breakout frequency (McConville & Wetherbee, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diatoms typically dominate both the phytoplankton and the sea-ice spring blooms, while flagellates, dinoflagellates, and picoeukaryotes usually dominate in late summer (Tremblay et al, 2009;Moran et al, 2012;van Leeuwe et al, 2018). Some diatom species, such as Shionodiscus bioculatus (formerly Thalassiosira bioculata) (Alverson et al, 2006) and Fragilariopsis cylindrus, are sea-ice associated and have been observed both in the water column and in the ice (von Quillfeldt, 2000).…”
Section: Introductionmentioning
confidence: 99%